Future climate change and impacts on water resources in the Upper Blue Nile basin. Issue 2 (30th December 2021) - Takele, Gebiyaw Sitotaw; Gebrie, Geremew Sahilu; Gebremariam, Azage Gebreyohannes; Engida, Agizew Nigussie
Abstract: This study aims to assess the impact of climate change on the water resources of the Upper Blue Nile basin using an integrated climate and hydrological model. The impact of climate change on water resources is being assessed using the regional climate model (RCM) under the representative concentration pathway (RCP4.5 and RCP8.5) scenarios and the Soil and Water Assessment Tool (SWAT) hydrological model. Future climate scenarios have been developed for the 2030s (2021–2040) and the 2050s (2041–2060). The study found that the projected rainfall shows a decreasing trend and is not statistically significant, while the temperature shows an increasing trend and is statistically significant. Due to the sharp rise in temperature, the annual evapotranspiration increased by about 10.4%. This and the declining trend of rainfall will reduce streamflow up to 54%, surface runoff up to 31%, and water yield up to 31%. Climate change causes seasonal and annual fluctuations in the water balance components. However, the projected seasonal changes are much greater than the annual changes. Therefore, the results of this study will be useful to basin planners, policymakers, and water resources managers in developing adaptation strategies to offset the adverse effects of climate change in the Upper Blue Nile basin. HIGHLIGHTS: The baseline rainfall trend is increasing but insignificant, whereas the ensembled regional climate model (RCM)-simulated rainfall trend is decreasing. Despite some RCMs having a seasonal shift in rainfall, there is no discernible seasonal movement in surface runoff and water production. Ensembled rainfall, streamflow, surface runoff, and water output reveal a decrease in the 2030s and 2050s climate conditions. Graphical Abstract